2014
DOI: 10.1002/cssc.201301374
|View full text |Cite
|
Sign up to set email alerts
|

Excavated Fe‐N‐C Sites for Enhanced Electrocatalytic Activity in the Oxygen Reduction Reaction

Abstract: Platinum (Pt) is the best electrocatalyst for the oxygen reduction reaction (ORR) in hydrogen fuel cells, but it is an extremely expensive resource. The successful development of a cost-effective non-Pt ORR electrocatalyst will be a breakthrough for the commercialization of hydrogen-air fuel cells. Ball milling has been used to incorporate metal and nitrogen precursors into micropores of carbon more effectively and in the direct nitrogen-doping of carbon under highly pressurized nitrogen gas in the process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 37 publications
2
24
0
4
Order By: Relevance
“…[48,52,129] Maldonado and Stevenson [129] performed analysis of the heterogeneous decomposition of hydrogen peroxide at Ndoped carbon nanofibers (N-CNFs) and observed that the rate of decomposition of hydrogen peroxide on N-CNFs was tremendously increased by about 100 fold relative to the nondoped CNFs.W eo bserved in ar ecent study that metalfree NC catalysts disproportionate hydrogen peroxide nearly as fast as Fe-N x /C catalysts and that decomposition of hydrogen peroxide is an important reaction step in the reduction of O 2 on this type of catalysts. [9,16,38,44,47,48,65,109,126,136,163,164] In Figure 12 c, the catalytic activity of am etal-free NC catalyst is seen to be extremely enhanced in the presence of transition metals. [9,16,38,44,47,48,65,109,126,136,163,164] In Figure 12 c, the catalytic activity of am etal-free NC catalyst is seen to be extremely enhanced in the presence of transition metals.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…[48,52,129] Maldonado and Stevenson [129] performed analysis of the heterogeneous decomposition of hydrogen peroxide at Ndoped carbon nanofibers (N-CNFs) and observed that the rate of decomposition of hydrogen peroxide on N-CNFs was tremendously increased by about 100 fold relative to the nondoped CNFs.W eo bserved in ar ecent study that metalfree NC catalysts disproportionate hydrogen peroxide nearly as fast as Fe-N x /C catalysts and that decomposition of hydrogen peroxide is an important reaction step in the reduction of O 2 on this type of catalysts. [9,16,38,44,47,48,65,109,126,136,163,164] In Figure 12 c, the catalytic activity of am etal-free NC catalyst is seen to be extremely enhanced in the presence of transition metals. [9,16,38,44,47,48,65,109,126,136,163,164] In Figure 12 c, the catalytic activity of am etal-free NC catalyst is seen to be extremely enhanced in the presence of transition metals.…”
Section: Methodsmentioning
confidence: 96%
“…[69] unzipped MWCNTs to expose Fe, and by afurther treatment step with NH 3 ,they were able to transform them into av ery active and stable catalyst for O 2 reduction under both acidic and alkaline conditions.T op robe whether Fe was involved in the active sites,t he authors added CN À ions to the electrolyte and observed ad egeneration of activity,t hus suggesting that Fe was directly involved as part of the active site(s). [163] 5. [163] 5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al utilized a ball milling method to excavate the ORR active sites embedded in Fe-modified N-doped carbon nanofibers by pulverization. The facile ball-milling process resulted in a significant enhancement in the ORR activity and the selectivity of the obtained catalyst owing to the high exposure of the metalbased catalytically active sites [14]. In 2011, a highly active electrocatalyst (Fe-N-C) reported by Wu et al has shown a maximum power density of 0.55 W cm À2 and excellent stability of 700 h of long-term testing, which is one of the best active nonprecious metal catalysts to date [15].…”
Section: Introductionmentioning
confidence: 99%